Assessment of work environment vs. feeling of threat and aggravation of stress in job of a high risk - An attempt of organizational intervention - Marta Stasiła-Sieradzka; Agata Chudzicka-Czupała; Damian Grabowski; Małgorzata Dobrowolska (Nofer Institute of Occupational Medicine, 2018)
Background The main purpose of this article was to examine, whether and to what extend an assessment of work environment and feeling of threat are associated with stress at work performed in health- and life-threatening conditions. Previous studies of the determinants of occupational stress have been carried out in relation to representatives of different occupational groups that are not, however, representatives of one organization. The research was also meant to provide practical guidance for a particular employer. Material and Methods The study was carried out in the factory of explosives. It involved 95 randomly selected employees of the production departments. Subjective evaluation of work was performed by the examined persons in the Areas of Worklife Survey. It allows to assess the functioning of the employee in the workplace and to recognize the discrepancies between the requirements of the organization and the needs, aspirations and abilities of the examined person. Feeling of insecurity at work was defined by using the Feeling of Danger at Work Survey. The level of stress was assessed using the Perceived Stress Scale (PSS-10). Results The workload and feeling of danger are relevant to the stress felt by the employees. The workload is also the mediator of the relations between the sense of danger and the stress felt by the examined employees. Conclusions At the level of manufacturing process management in an organization, there is a need to reduce the negative impact of physical and mental strain associated with haste and uncertainty. Med Pr 2018;69(1):45-58